2009
DOI: 10.1140/epjb/e2009-00142-3
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of standing waves generated by a point defect in epitaxial graphene

Abstract: Using scanning tunneling microscopy (STM) and Fourier Transform STM (FT-STM), we have studied a point defect in an epitaxial graphene sample grown on silicon carbide substrate. This analysis allows us to extract the quasiparticle energy dispersion, and to give a first experimental proof of the validity of Fermi liquid theory in graphene for a wide range of energies from -800 meV to +800 meV . We also find evidence of a strong threefold anisotropy in the standing waves generated by the defect. We discuss possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 28 publications
8
73
0
Order By: Relevance
“…We emphasize that a few publications have tried so far to give a description of the different features in the experimental FT-LDOS images of epitaxial graphene. 27,28,30,31 However, a poor resolution in k space was partly limiting such analysis. In a report published in 2008, some of us have shown that it was possible to evidence fine structures in FT-LDOS data with improved quality.…”
Section: High-resolution Stm Results On Monolayer Graphene On Sicmentioning
confidence: 99%
See 2 more Smart Citations
“…We emphasize that a few publications have tried so far to give a description of the different features in the experimental FT-LDOS images of epitaxial graphene. 27,28,30,31 However, a poor resolution in k space was partly limiting such analysis. In a report published in 2008, some of us have shown that it was possible to evidence fine structures in FT-LDOS data with improved quality.…”
Section: High-resolution Stm Results On Monolayer Graphene On Sicmentioning
confidence: 99%
“…[27][28][29][30][31][32][34][35][36][37][38][39][40][41][42] Because of the topology of the FS pockets, coupling between states with opposite q F in each pocket [ Fig. 1(d)] is highly favored.…”
Section: Quasiparticle Scattering In Graphene: Intravalley and Imentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic-field strength is assumed weak enough so that we could take the energy levels as spin degenerate. The dispersion curves can be experimentally observed via scanning tunnelling microscopy (Simon et al 2009). The tunnelling current flowing through the microscope tip is proportional to the LDOS given by…”
Section: Modelmentioning
confidence: 99%
“…Not surprisingly, then, many theory groups have recently devoted attention to the prospect of RKKY interactions. [63][64][65][66][67][68][69][70][71][72][73][74] They and others pointed out a variety of complicating issues and idiosyncrasies of mono-layer graphene, such as the bipartite nature of the lattice (leading to ferromagnetic or repulsive coupling for impurities on the same hexagonal, Bravais sublattice of the honeycomb graphene lattice 63,64 and antiferromagnetic or attractive coupling when on opposite Bravais sublattices, 64,65,68,69 ), the vanishing density of states at the Fermi level in undoped and ungated lattices, the suppression of backscattering (leading to R −3 rather than R −2 decay 75 ), 63,64 the role of electron-electron interactions, 70 etc. Usually the adsorbates are taken in atop sites but sometimes in bridge sites above bonds or hollow sites at the center of the hexagon.…”
mentioning
confidence: 99%